2016
DOI: 10.1111/anae.13606
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomised study of a rigid video‐stylet vs. conventional lightwand intubation in cervical spine‐immobilised patients

Abstract: Compared with a lightwand which is used blind, Optiscope , a rigid video-stylet, can provide direct imaging of airway structures, potentially offering improved conditions in cervical spine-immobilised patients. We randomly assigned 168 patients who required cervical immobilisation during tracheal intubation to use of the Optiscope or the lightwand. The initial intubation success rate (95% CI) was 90 (82-95)% with the Optiscope and 87 (78-93)% with the lightwand (p = 0.626). Median (IQR [range]) intubation time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…In a previous study, difficult intubation as defined in the present study was observed in 10% of patients who were intubated using the Optiscope™ with cervical spine immobilization [10]. To reproduce the proportion of cases of difficult intubation with the Optiscope™ with a 95% confidence interval (CI) and a margin of error of 0.05, at least 159 patients were required in this study.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…In a previous study, difficult intubation as defined in the present study was observed in 10% of patients who were intubated using the Optiscope™ with cervical spine immobilization [10]. To reproduce the proportion of cases of difficult intubation with the Optiscope™ with a 95% confidence interval (CI) and a margin of error of 0.05, at least 159 patients were required in this study.…”
Section: Discussionmentioning
confidence: 84%
“…In this study, difficult intubation with the Optiscope™ was defined as an intubation duration of more than 90 s or failed intubation on the first attempt. In a previous study comparing clinical performance between the Optiscope™ and Surch-Lite™ lightwand (Aaron Medical, St. Petersburg, FL, USA), [10] an intubation duration of 90 s corresponded to the 95th percentile. Therefore, we set the cutoff point of difficult intubation with the Optiscope™ as 90 s. This study had several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 3 5 ] Moreover, in patients with difficult airways or limited cervical motion, a rigid video-stylet performs better than conventional airway devices. [ 6 9 ] However, deterioration of the view might lead to intubation failure, resulting in multiple intubation attempts, a longer intubating time, and desaturation. [ 1 , 5 ] Therefore, unlike the conventional laryngoscope, decreased oral secretion might provide the advantage of better visualization of the rigid video-stylet.…”
Section: Introductionmentioning
confidence: 99%